2021
DOI: 10.1016/j.jpsychires.2020.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic reactions during the COVID-19 pandemic – The contribution of posttraumatic growth attributed to prior trauma

Abstract: Trauma survivors who suffer from posttraumatic stress disorder (PTSD) symptoms may be particularly vulnerable when facing the COVID-19 pandemic. Yet trauma exposure may also lead to salutogenic outcomes, known as posttraumatic growth (PTG). Nevertheless, the implications of PTG attributed to prior trauma, for trauma survivors' adjustment when facing additional stressors, are unclear. Addressing this gap, 528 Israeli trauma survivors were assessed for PTG and PTSD symptoms attributed to prior trauma, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 70 publications
2
44
0
4
Order By: Relevance
“…To capture distress due to the COVID-19 pandemic, we modified the original PDI instruction (i.e., “A lot has happened during the 100 days since the outbreak of the COVID-19 epidemic in our society. To what extent have you experienced the following items during the COVID-19 epidemic?”) [ 28 , 29 ]. The response options ranged from 0 (not at all true) to 4 (extremely true), and the ratings were summed to calculate the total score of peritraumatic distress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To capture distress due to the COVID-19 pandemic, we modified the original PDI instruction (i.e., “A lot has happened during the 100 days since the outbreak of the COVID-19 epidemic in our society. To what extent have you experienced the following items during the COVID-19 epidemic?”) [ 28 , 29 ]. The response options ranged from 0 (not at all true) to 4 (extremely true), and the ratings were summed to calculate the total score of peritraumatic distress.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, trauma-related mental health problems due to COVID-19 such as post-trauma stress disorder and traumatic stress also has been examined. The COVID-19 pandemic creates substantial traumatogenic events for everyone, from confirmed patients and healthcare workers to the general public [ 28 , 29 , 30 ]. Nevertheless, trauma-related reactions and posttraumatic stress disorder (PTSD) due to the novel coronavirus have been addressed relatively less compared to the general psychological problems such as depression and anxiety [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous studies found that more than half of survivors of severe acute respiratory syndrome (SARS) were diagnosed with PTSD in the post-SARS era (6) and 39% (95% CI: 31-47%) of the Middle East respiratory syndrome (MERS) survivors developed PTSD after 6 months of being discharged from hospitals (7). Many COVID-19 survivors experience physical and mental distress symptoms such as dyspnea, acute respiratory distress (ARDS), gatism, alterations of conscious states, and traumatic medical treatments (e.g., tracheotomy) (4, 8), that could trigger PTSS and contribute to lowered quality of life (QOL), functional impairment, frequent rehospitalizations, and financial strain, and/or increased risk for depression, insomnia, and anxiety (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Either factually or due to the limitation mentioned above, a very consistent finding in the current literature is the resilience to PTSD or other forms of psychiatric distress found in the older age group compared to the younger ones [ 11 20 ]. Most of studies link being female to higher incidence of PTSD [ 16 , 19 21 ]. Further, there is the incidence of enhanced PTSD symptoms if the patients have an existing chronic illness/non-communicable disease [ 18 , 22 , 23 ].…”
Section: Main Textmentioning
confidence: 99%